Nanowires self-assemble into β-MnO2 nanospheres to form crosslinking 3D hierarchical porous networks: with template-free fabrication and good supercapacitive performance over a broad temperature range. Issue 19 (1st September 2021) - Yu, Li-Li; Xu, Wei-Ling; Zhang, Jian-Guo; Li, Shuang; Li, Rong-Bing; Zhao, Jing-Tai
Abstract : Template-free fabrication of nanowires self-assembling into nanospheres and crosslinking into 3D hierarchical porous β-MnO2 networks with good supercapacitive performance over a broad temperature range. Abstract : Porous nanospheres self-assembled from nanowires interconnecting with each other to form 3D hierarchical mesoporous networks of beta-MnO2 (β-MnO2 ) are successfully prepared, with a high yield, at room temperature with a template-free approach. Due to its high specific surface area, abundant pores, interconnected structure, as well as a great length/diameter ratio, the as-prepared β-MnO2, in 0.5 M Na2 SO4, exhibits a good electrochemical performance at a wide temperature range of 5–80 °C. The ion conductivity of the electrolytes proved to be the main factor for the enhancement of the surface controlled capacitance of β-MnO2 as the temperature increased. Therefore, when assembled with an AC to form an asymmetrical supercapacitor, β-MnO2 //AC can derive 12.9 W h kg −1 at 9.5 kW kg −1 with a superior cycling stability (91.8%, after 5000 cycles at 5 A g −1 ) at 5–50 °C, even after suffering from a sudden temperature change. This proves that the as-formed MnO2 is a promising electrode material for supercapacitor applications requiring a high-performance over a broad temperature range.